The effect of contralateral noise on the middle evoked response - GUNJA, NAZNEEM YAKUB (Journal of All India Institute of Speech and Hearing)
The present study was aimed at investigating whether there is any effect of contralateral noise on the latency and amplitude of the VI, VII and Po peak. Simultaneously, the study was also aimed at seeing if there was any change in the amplitude and latency of the V peak when measured using patient response interval of 10 msec, and 20 msec. And finally, the study attempted to find out if there was any difference between the combined amplitude of middle response and the binaural amplitude response.